Shared decision making during antenatal counselling for anticipated extremely preterm birth. Issue 4 (3rd December 2018) - Barker, Conor; Dunn, Sandra; Moore, Gregory P; Reszel, Jessica; Lemyre, Brigitte; Daboval, Thierry
Abstract: Objective(s): To explore health care providers' (HCPs) perceptions of using shared decision making (SDM) and to identify facilitators of and barriers to its use with families facing the anticipated birth of an extremely preterm infant at 22 +0 to 25 +6 weeks gestational age. Study Design: Qualitative descriptive study design: we conducted interviews with 25 HCPs involved in five cases at a tertiary care centre and completed qualitative content analysis of their responses. Results: Nine facilitators and 16 barriers were identified. Facilitators included: a correct understanding of this process and how to apply it, a belief that parents should be the decision makers in these situations, and a positive outlook toward using SDM during antenatal counselling. Barriers included: HCPs' misunderstandings of how and when to apply SDM during antenatal counselling, challenges using the process for cases at the lower end of the gestational age range, fear of the negative emotions and stress parents face when making decisions, and HCPs' uncertainty about their ability to properly apply SDM. Conclusion(s): This study identified facilitators and barriers to use of SDM during antenatal counselling for anticipated birth of extremely preterm infants that can be used to inform development of tailored strategies to facilitate future implementation of shared decision making in this area.